The Effect of Project-Based Learning (PjBL) with STEM Approach on Students’ Metacognitive Awareness, Conceptual Understanding, and Biology Problem-Solving Ability - Nia Febrianti; Firdaus Daud; Yusminah Hala; Muhiddin Palennari; Nurhayati B (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze effect of the Project-Based Learning model based on the STEM approach on metacognitive awareness, conceptual understanding, and biology problem-solving abilities of grade XI students of SMA Negeri 13 Bone. The novelty of this study lies in integration of PjBL-STEM which simultaneously measures three high-level cognitive aspects in one experimental design. This study is a quasi-experimental study with a Pretest-Posttest Nonequivalent Control Group Design. The sample consisted of two classes (n=72) using a purposive sampling technique. Instruments included the MAI questionnaire, an essay test based on the SOLO taxonomy (prestructural to expanded abstract), and a problem-solving test based on Polya's stages, all of which have met high validity and reliability. Data were analyzed using ANCOVA (α = 0.05). The results showed that PjBL-STEM had a significant effect on metacognitive awareness (p=.004), conceptual understanding (p=.01), and biology problem-solving ability (p<.001). The experimental group showed a higher average increase compared to the control, indicating the effectiveness of PjBL-STEM in enhancing systematic and reflective thinking to support development of 21st century skills. Limitations of this study include quasi-experimental design without full randomization and sample size limited to one school. Further research is needed to test the generalizability of the findings.